PENGEMBANGAN VIDEO TUTORIAL PRODUKSI ANIMASI PEMBELAJARAN SEKOLAH DASAR MENGGUNAKAN MICROSOFT POWER POINT - Muhamamad Ragil Kurniawan (JURNAL PEDAGOGIK PENDIDIKAN DASAR, 2020)
This study attempts to: (1) develop media tutorials in making of primary school animated learning use application Microsoft power point, (2) know feasibility media tutorials in making of primary school animated learning use application Microsoft power point. This is a Research and Development Research (R D), which are generally trough four stages, namely: study introduction, design development, product development, and product evaluation. Data collection was in the form of sheets of material validation, media experts and users to know the feasibility of video tutorial media. The product of the development is in the form of video tutorials media that can be stored in compact disk (CD). The research results show as follows: (1) media tutorial video developed was for teaching the ability for the production of simple animation in primary school learning, (2) evaluation results of material experts obtains a judgment 3.7 (good category) by inference worth to be used, (3) evaluation of media experts obtains a judgment 4.1 (god category) by inference worth to be used, (4) evaluation results by users get average 4.3 (very good category) by inference worth to be used.